1993
DOI: 10.4141/cjas93-016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine on carcass characteristics and joint-cartilage soundness in finishing pigs

Abstract: of ractopamine in pig diets significantly increased average daily gain (P < 0.005) and decreased feed to gain ratio (P < 0.001), with no effect on daily feed intake. Ractopamine feeding increased total lean (P < 0.001) and decreased total bone (P < 0.05) and total fat content (P < 0.001) of carcasses. The decreased fat content was largely due to the reduction of subcutaneous fat (P < 0.001). Cartilage visual scores and cartilage uronic acid concentrations of weight-bearing areas of humeral and femoral condyles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Average daily gain was not affected by RAC in this study, which is consistent with reports by Aalhus et al (1990) and Yen et al (1990). However, a number of other studies (He et al, 1993;Crome et al, 1996;Xiao et al, 1999) have reported that RAC increased ADG.…”
Section: Growth Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…Average daily gain was not affected by RAC in this study, which is consistent with reports by Aalhus et al (1990) and Yen et al (1990). However, a number of other studies (He et al, 1993;Crome et al, 1996;Xiao et al, 1999) have reported that RAC increased ADG.…”
Section: Growth Performancesupporting
confidence: 92%
“…Paylean, the trade name for the repartitioning agent ractopamine hydrochloride (RAC; Elanco Animal Health, Greenfield, IN), was approved by the FDA for use in finishing swine in 1999. Research has shown that RAC improves live performance in swine by increasing ADG (Stites et al, 1991;He et al, 1993;Dunshea et al, 1998), decreasing ADFI (Crenshaw et al, 1987;Aal-1361 LEAN than in FAT pigs, phenotype did not (P = 0.08) affect overall ADG. Dietary RAC decreased (P ≤ 0.05) ADFI over the 28-d feeding trial, as well as in wk 2, 3, and 4, but intake was not (P > 0.20) affected by phenotype.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ractopamine has been shown to improve the efficiency of feed utilization in pigs (WATKINS et al, 1990;HE et al, 1993;DUNSHEA et al, 1998). In the present study, ractopamine treatment resulted in an improvement in the efficiency of protein deposition.…”
Section: Validation Studysupporting
confidence: 52%
“…Ractopamine has been shown to improve the efficiency of feed utilization (FGR) in pigs (Watkins et al, 1990;He et al, 1993;Dunshea et al, 1998). In the present study, ractopamine treatment resulted in an improvement in both feed efficiency and the efficiency of PE.…”
Section: Efficiency or Energy And Protein Depositionmentioning
confidence: 49%